2019
DOI: 10.1093/jhered/esz032
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of Global Domestic Horse Biogeography Using Historic Landrace Chinese Mongolian Populations

Abstract: The Mongolian horse is one of the oldest extant horse populations and although domesticated, most animals are free-ranging and experience minimal human intervention. As an ancient population originating in one of the key domestication centers, the Mongolian horse may play a key role in understanding the origins and recent evolutionary history of horses. Here we describe an analysis of high-density genome-wide single-nucleotide polymorphism (SNP) data in 40 globally dispersed horse populations (n = 895). In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The F ROH statistic proposed by McQuillan et al 83 was then calculated, whereby the total length of ROH covering an individual animal's genome (L ROH ) is divided by the length of the autosomal genome (L AUTO ); F ROH = L ROH / L AUTO . Here, consistent with other equine studies 84,85 we used the length of the equine autosomal genome (assembly EquCab 2) 86 as 2,242,960 kb (www.ncbi.nlm.nih.gov/genome/145?genome_assembly_id=22878).…”
Section: Methodsmentioning
confidence: 99%
“…The F ROH statistic proposed by McQuillan et al 83 was then calculated, whereby the total length of ROH covering an individual animal's genome (L ROH ) is divided by the length of the autosomal genome (L AUTO ); F ROH = L ROH / L AUTO . Here, consistent with other equine studies 84,85 we used the length of the equine autosomal genome (assembly EquCab 2) 86 as 2,242,960 kb (www.ncbi.nlm.nih.gov/genome/145?genome_assembly_id=22878).…”
Section: Methodsmentioning
confidence: 99%
“…As an important breed in northern China, Mongolian horses have rich genomic diversity ( 21 ) and have a variety of excellent traits, such as adaptability, cold resistance, roughage resistance, disease resistance, and good stamina ( 22 , 23 ). Thoroughbred horses, a horse species bred in 17th-century Britain, were manually selected to meet the desired conditions of speed, temperament, and body size ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…gaitedness, strong hooves and black coat colour) may have contributed to the observed genomic diversity among the Chinese Mongolian populations. Furthermore, these ve Chinese Mongolian as well as two other Asian populations (the Mongolian horse populations in Mongolia and Tuva) were genetically similar to each other but distinct from other global horse populations and were positioned between two large regional groups (European and American/Iberian/Middle Eastern) in the PCA analysis [5]. These results therefore lead to the hypothesis that natural and arti cial selection will have left signatures in the Chinese Mongolian populations for long-term environmental adaptation when compared to other global horse populations.…”
Section: Introductionmentioning
confidence: 84%
“…We recently suggested that Mongolian horse populations may preserve ancient genomic variants that do not exist in other global horse breeds [5] as their paternal lineages can be dated to the early domesticates, at least 1400 YBP [40] . Therefore, a second possible explanation is that DOM2 horses did not replace all locally domesticated horse populations and Chinese Mongolian (and Mongolian and Tuva) horses may be the result of an entirely separate domestication event not linked to the Volga-Don origins.…”
Section: Selection Signals Relating To Geographic Originmentioning
confidence: 99%
See 1 more Smart Citation